Training in book writing with high school students in Depok. - Kurniawan, Angga (Yayasan Putra Adi Dharma, 2023)
This study aimed to investigate the effectiveness of a book writing training program for high school students in Depok. The initiative sought to enhance students' writing skills and foster their creativity by guiding them in the process of conceptualizing, drafting, and editing their own books. High school students often face challenges when it comes to expressing their ideas in written form, and this training program was designed to address these hurdles. The training program included various components such as writing workshops, one-on-one guidance from experienced authors, and the provision of writing resources. A mixed-methods approach, combining surveys and writing assessments, was employed to evaluate the program's impact on the students' writing abilities and creative expression. Preliminary findings indicate that the book writing training program positively influenced students' writing skills and stimulated their creative thinking. The students reported increased confidence in their ability to express themselves through the written word. This research provides valuable insights into the potential benefits of creative writing training for high school students, contributing to the enhancement of their communication and creative skills.